Curcumin regulated shift from Th1 to Th2 in trinitrobenzene sulphonic acid-induced chronic colitis - Zhang Ming; Deng Chang-sheng; Zheng Jia-ju; Xia Jian (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the therapeutic effects of curcumin (Cur) on trinitrobenzene sulphonic acid (TNBS)-induced colitis and the effects of Cur on the balance of Th1/Th2 cytokines. Methods: Colitis was induced by TNBS and treated with Cur (30 mg·kg-1·d-1, ip), dexamethasone (Dex, 2 mg·kg-1·d-1), or Cur plus dexamethasone (Cur+Dex, 30 mg·kg-1·d-1 Cur ip+2 mg·kg-1·d-1 Dex, ip). mRNA in colon mucosa were detected by real·time quantitative polymerase chain reaction. Intracellular cytokines were detected by flow cytometry and concentrations of cytokines in sera were detected by enzyme·linked immunosorbent analysis. Results: Both Cur and Dex improved body weight loss, ameliorated histological images and decreased macroscopic score and myeloperoxidase activity. Cur decreased the expression of Th1 cytokines (IL-12, IFN-γ, TNF-α, IL-1) and increased the expression of Th2 cytokines (IL-4 and IL-10) in colon mucosa. Cur also increased the proportion of IFN-γ/IL-4 in splenocytes and circulation. Dex and Cur+Dex decreased the expression of Th1 cytokines but could not increase the expression of Th2 cytokines and the proportion of IFN-γ/IL-4. Conclusion: Cur exerted therapeutic effects on colitis by regulating the shift from Th1 to Th2.